TANTANGAN PEMBELAJARAN DI SEKOLAH DASAR DI DESA PADA MASA PPKM DI BALI - Putu Eka Dambayana Suputra; I Gede Budasi; I Made Suta Paramarta (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2021)
Abstract This social service aimed at administering free English instructional assistance and course to both teachers and students in elementary schools located in rural areas in Bali. The program has been conducted for 4 years starting from 2018. Our focus in this paper was identifying the challenges faced by the students during the program conducted from 13 July to 31 August 2021 since the teacher was a non-English department graduate and most students needed English course assistance. All teachers teaching English in elementary schools we helped majored Elementary Education degree. Besides, this program was to help the students to prepare their English competencies and skills onto junior high level. The program was conducted for six months once a week online via WhatsApp group with the class teacher and the students. This was because we still faced Covid-19 Pandemics. The results show that the students still find challenges in understanding the materials and assignments, and learning participation. Abstrak Program Pengabdian Kepada Masyarakat ini bertujuan memberikan pendampingan dan bimbingan belajar gratis kepada guru dan siswa Sekolah Dasar (SD) di pedesaan di Bali. Program serupa telah dilaksanakan selama 4 tahun sejak 2018. Fokus artikel berikut adalah mengidentifikasi tantangan-tantangan yang dihadapi siswa selama program yang dilaksanakan pada 13 Juli sampai 31 Agustus 2021. Guru-guru pengajar Bahasa Inggris di sekolah-sekolah yang kami bantu memiliki keahlian bidang non bahasa Inggris yakni Pendidikan Guru Sekolah Dasar (Guru Kelas) dan sebagian besar siswa membutuhkan bimbingan belajar Bahasa Inggris. Program ini juga dimaksudkan untuk mempersiapkan kemampuan dan keterampilan bahasa Inggris siswa pada jenjang Sekolah Menengah Pertama (SMP). Program dilaksanakan selama 6 minggu melalui moda daring dengan grup WhatsApp karena dilaksanakan pada masa Pandemi Covid-19. Hasil menunjukkan bahwa siswa masih menghadapi tantangan dalam memahami materi dan tugas-tugas, dan partisipasi belajar.